Knowledge Sharing Through Informal Communication Among Malaysian Civil Servants - Akmal Afzan, Nik Maizatul (2011)
This paper reports a study of whether knowledge sharing through informal communication can have impact towards the government workforce. This study is concentrated on government workers in Putrajaya, specifically on the Malaysian Immigration department. In this paper, it investigates the beneficial of informal communication to the government workers. The positive and negative sides of knowledge sharing through informal communication are also included in this report.